Succinic acid composition and polyester and polyester composite material prepared from succinic acid composition

By using succinic acid compositions containing sulfate and phosphorus compounds, the problems of poor thermal stability and equipment corrosion in thermoforming processing of PBS are solved, and efficient production of low acid value and high viscosity polyester is achieved, improving product quality and equipment protection effect.

CN119505195APending Publication Date: 2025-02-25ZHUHAI KINGFA BIOMATERIAL CO LTD +2

Patent Information

Application Number
CN202411701210.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing polybutylene succinate (PBS) has poor thermal stability during thermoforming and is easy to distribute acidic substances, resulting in equipment corrosion and difficult to meet the needs of the application side.

Method used

A succinic acid composition is used, which includes succinic acid, a sulfate-containing compound and a phosphorus compound. By combining a specific content of sulfate and phosphorus compounds, the production efficiency of the polyester is improved, the acid value and viscosity are reduced, and the corrosion to the equipment is reduced.

Benefits of technology

It realizes high reactive, low acid value and high viscosity polyester production, reduces the corrosion of polyester composite materials on the equipment and improves product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005153348070000151
    Figure BDA0005153348070000151
  • Figure BDA0005153348070000231
    Figure BDA0005153348070000231
  • Figure BDA0005153348070000241
    Figure BDA0005153348070000241
Patent Text Reader

Abstract

The invention provides a succinic acid composition as well as polyester and a polyester composite material prepared from the succinic acid composition. The succinic acid composition comprises succinic acid, a compound containing sulfate radicals and a phosphorus compound, the mass content of sulfate radicals in the succinic acid composition is 240 to 500 ppm; the mass content of the phosphorus element in the succinic acid composition is 0.5 to 40 ppm. According to the present invention, by compounding the sulfate radical-containing compound and the phosphorus compound with the specific content, the polyester is prepared by using the succinic acid composition as the raw material, such that the production efficiency of the polyester can be ensured, the polyester with characteristics of low acid value and high viscosity can be obtained, and the corrosion of the polyester or the composition thereof on the metal equipment can be reduced during the polyester composite material extrusion process; the quality of the polyester composite material is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyester preparation, and specifically relates to a succinic acid composition and polyester and polyester composite material prepared therefrom. Background Art

[0002] Polybutylene succinate (PBS) is made from succinic acid and 1,4-butanediol through esterification and polycondensation, and can be processed on ordinary molding equipment by extrusion, injection molding, blow molding, spinning, blister molding, lamination, foaming, etc. The product has a wide range of uses, and its main application areas include: packaging, such as plastic wrap, express bags, disposable tableware, etc.

[0003] However, pure PBS resin is often difficult to meet the needs of the application end due to its own performance defects. Therefore, it is usually necessary to blend and modify PBS resin and other materials, and process them into polyester composite materials that meet the needs of terminal applications through thermoforming processes such as twin-screw extrusion. Since PBS resin itself has a certain number of carboxyl functional groups, and PBS resin has poor thermal stability, it is easily decomposed by heat during processing to release acidic substances, and acidic substances can corrode metal equipment. Therefore, for polyester composite materials that need to be prepared by thermoforming, and when the thermoforming equipment includes metal parts, for example, a screw extruder is used for thermoforming processing, after the screw extruder produces polyester composite materials for a period of time, it is easy to cause serious corrosion of the screw extruder. The corrosion of the screw extruder will weaken the processing capacity of the screw extruder, such as the reduction of shear and dispersion capabilities, and on the other hand, it will also cause foreign matter points to be generated in the polyester composite material, resulting in a decrease in product quality.

[0004] Therefore, it is an urgent problem to be solved in the art to develop a succinic acid composition that has high reaction activity, can improve polyester production efficiency, obtain polyester with low acid value and high viscosity, and can reduce the corrosion of polyester composite materials to equipment during the thermoforming process. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a succinic acid composition and polyester and polyester composite materials prepared therefrom. The polyester prepared by using the succinic acid composition as a raw material has high reaction activity and high polyester production efficiency, and the obtained polyester has low acid value and high viscosity; and when the polyester composite material is prepared by a thermoforming process, the degree of corrosion to the equipment is small.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a succinic acid composition, comprising succinic acid, a compound containing sulfate and a phosphorus compound; the mass content of sulfate in the succinic acid composition is 240 to 500 ppm; the mass content of phosphorus in the succinic acid composition is 0.5 to 40 ppm.

[0008] In the present invention, the compound containing sulfate groups can improve the esterification efficiency of succinic acid, thereby improving the production efficiency of polyester, and is conducive to obtaining polyester with low acid value and high viscosity and polyester composite materials, and the polyester with low acid value is also conducive to reducing the corrosion of polyester to equipment during processing; and the phosphorus compound, based on the effect of electron coordination, the phosphorus atom can form a structurally stable metal complex with metal ions by donating electron pairs, and the metal complex covers the metal surface, which can play a protective role on the metal and slow down the corrosion of the polyester material to metal equipment during processing; by compounding the compound containing sulfate groups with a specific content and the phosphorus compound, the polyester is prepared with the succinic acid composition as a raw material, which can ensure the production efficiency of the polyester and obtain a polyester with a lower acid value and a whiter color. When the polyester composite material is prepared with the polyester as the base resin, the corrosion of the polyester to metal equipment can be reduced, and the quality of the polyester composite material can be ensured.

[0009] In the present invention, the mass content of sulfate in the succinic acid composition is 240 to 500 ppm, for example, 240 ppm, 245 ppm, 250 ppm, 255 ppm, 260 ppm, 265 ppm, 270 ppm, 275 ppm, 280 ppm, 285 ppm, 290 ppm, 295 ppm, 300 ppm, 305 ppm, 310 ppm, 315 ppm, 320 ppm, 325 ppm, 330 ppm, 335 ppm, 340 ppm pm, 345ppm, 350ppm, 355ppm, 360ppm, 365ppm, 370ppm, 375ppm, 380ppm, 385ppm, 390ppm, 395ppm, 400ppm, 405ppm, 410ppm, 415ppm, 420ppm, 430ppm, 440ppm, 450ppm, 460ppm, 470ppm, 480ppm, 490ppm, 500ppm or a range between any of the above values.

[0010] In the present invention, the mass content of the sulfate radical is low, the esterification efficiency is low, the residence time is long, the obtained polyester acid value is high, the viscosity is low, and thus equipment corrosion may be caused; the mass content of the sulfate radical is high, the corrosiveness to metals is high, and in an aqueous environment, it is easily soluble in water to form a sulfuric acid solution, and the released H + The ions make the solution acidic, further intensifying the corrosion of the metal.

[0011] In the present invention, the mass content of phosphorus in the succinic acid composition is 0.5 to 40 ppm, for example, it can be 0.5 ppm, 1 ppm, 2 ppm, 4 ppm, 6 ppm, 8 ppm, 10 ppm, 12 ppm, 14 ppm, 16 ppm, 18 ppm, 20 ppm, 22 ppm, 24 ppm, 26 ppm, 28 ppm, 30 ppm, 32 ppm, 34 ppm, 36 ppm, 38 ppm, 40 ppm or a range between any of the above values.

[0012] In the present invention, if the mass content of the phosphorus element is too low, it will cause serious corrosion to the equipment during the thermal processing; if the content is too high, it will passivate the activity of the catalyst, resulting in a decrease in catalytic efficiency, and then lead to a prolonged residence time of the polymerization reaction, an increase in the acid value of the polyester, and a yellowing of the color, which will also cause a certain degree of corrosion.

[0013] Preferably, the mass content of sulfate in the succinic acid composition is 320 to 480 ppm, preferably 370 to 420 ppm.

[0014] Preferably, the mass content of phosphorus in the succinic acid composition is 2 to 25 ppm, more preferably 5 to 20 ppm.

[0015] Preferably, the sulfate-containing compound comprises sulfuric acid and / or sulfate salts.

[0016] Preferably, the sulfate includes any one or at least two of sodium sulfate, magnesium sulfate, potassium sulfate or iron sulfate.

[0017] Preferably, the phosphorus compound comprises any one or at least two of nucleic acid, phospholipid, dioctyl phosphate, diethyl phosphate, triethyl phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphoric acid, phosphorous acid or sodium phosphate. Preferably, the mass percentage of succinic acid in the succinic acid composition is ≥99.5%, for example, it can be 99.5%, 99.6%, 99.7%, 99.8%, 99.9% or the range between any of the above values; preferably, the mass percentage of succinic acid is ≥99.7%, and more preferably, the mass percentage of succinic acid is ≥99.8%.

[0018] In the present invention, the sulfate-containing compound and phosphorus compound in the succinic acid composition can be obtained by externally adding the sulfate-containing compound and phosphorus compound to obtain the succinic acid composition; or some compounds remain in the succinic acid during the preparation of succinic acid to form the succinic acid composition.

[0019] In the present invention, when the succinic acid composition is formed by some compounds remaining in succinic acid during the preparation of succinic acid, the preparation raw materials include petroleum resources or biomass resources.

[0020] In the present invention, the preparation method of the succinic acid composition includes microbial fermentation, chemical synthesis or external addition preparation; when microbial fermentation or chemical synthesis is adopted, the sulfate-containing compound and phosphorus compound can be derived from the residues of any substance containing sulfate or phosphorus element added during the preparation process.

[0021] For example, when the succinic acid composition is prepared by chemical synthesis using petroleum resources as raw materials, the compound containing sulfate groups can be electrolyte sulfuric acid used in the catalytic hydrogenation preparation process of maleic anhydride or sulfate added as needed.

[0022] When microbial fermentation is used, the phosphorus compound can be nucleic acid, phospholipids, etc. derived from microorganisms; it can also be diethyl phosphate, triethyl phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphoric acid, phosphorous acid or sodium phosphate, etc. added during the fermentation process.

[0023] The succinic acid composition is prepared by microbial fermentation using biomass resources as raw materials. The compound containing sulfate groups can be sulfuric acid added to adjust the pH value of the fermentation system or acidify succinate, or sulfate added externally as needed; the phosphorus compound can be a phosphorus compound remaining in the process of preparing succinic acid by microbial fermentation, or can also be an externally added phosphorus compound.

[0024] In the present invention, the biomass resources include plant resources and / or animal resources, preferably plant resources.

[0025] In the present invention, the plant resources refer to biomass resources that can convert the sun's light energy into starch or cellulose and store it through photosynthesis; the animal resources refer to biomass resources that grow and develop by preying on plants; the plant resources or animal resources also include products obtained by processing plant resources or animal resources.

[0026] In the present invention, illustratively, the plant resources include but are not limited to wood, rice straw, rice husk, rice bran, old rice, corn, sugarcane, cassava, corn nodes, cassava starch residue, bagasse, vegetable oil residue, barley, soybeans, food waste, etc.

[0027] In the present invention, the biomass resources need to be converted into a carbon source, and then the carbon source is used as a raw material to prepare a succinic acid stock solution, and then the succinic acid stock solution is purified to obtain the succinic acid composition; the method of converting into a carbon source includes but is not limited to chemical treatment, physical treatment, biological treatment, etc.; illustratively, the chemical treatment can be acid treatment (for example, treatment with strong acids such as sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid), alkali treatment, ammonia freezing, cooking and blasting treatment, solvent extraction treatment, supercritical fluid treatment, oxidant treatment, etc.; the physical treatment can be pulverization treatment, cooking and blasting treatment, microwave treatment, electron beam irradiation treatment, etc.; the biological treatment can be microbial treatment, enzyme treatment, etc.

[0028] In the present invention, the carbon source illustratively includes but is not limited to hexoses such as glucose, mannose, galactose, fructose, sorbose, tagatose, etc.; pentoses such as arabinose, xylose, ribose, xylulose, ribulose, etc.; disaccharides or polysaccharides such as pentosans, sucrose, starch, cellulose, etc., preferably glucose, fructose, xylose, and particularly preferably glucose.

[0029] In the present invention, the microorganisms used in the microbial fermentation method can produce dicarboxylic acids, and illustratively include: anaerobic bacteria, facultative anaerobic bacteria, aerobic bacteria, etc.; the anaerobic bacteria can be, for example, Anaerobiospirillum (US5143833A); the facultative anaerobic bacteria can be, for example, Actinobacillus (US5504004A), Escherichia (US5770435A), etc.; the aerobic bacteria can be, for example, Corynebacterium (Japanese Patent Publication No. 11-113588 or CN103183813A), which are introduced here as reference; preferably, aerobic bacteria such as Corynebacterium are used.

[0030] For example, taking microbial fermentation as an example, the preparation method of the succinic acid composition includes:

[0031] (1) using biomass resources as raw materials, and using a microbial fermentation method to prepare a succinic acid fermentation broth (using a conventional method, for example, it can be prepared by referring to the method in CN118459331A); filtering the succinic acid fermentation broth, adding an excess of calcium hydroxide to completely precipitate succinic acid, and filtering to obtain calcium succinate;

[0032] (2) mixing the calcium succinate obtained in step (1) with concentrated sulfuric acid, adjusting the pH value to 1.2-3 (for example, 1.2, 1.3, 1.5, 1.6, 1.8, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3 or any range between the above values), to obtain a succinic acid stock solution having a succinic acid mass concentration of 65-80 g / L (for example, 65 g / L, 68 g / L, 70 g / L, 72 g / L, 75 g / L, 78 g / L, 80 g / L or any range between the above values);

[0033] (3) subjecting the succinic acid stock solution obtained in step (2) to forward cross-flow extraction with a phosphate extractant to obtain a succinic acid-loaded organic phase; then, subjecting the succinic acid-loaded organic phase to reverse cross-flow extraction with water to obtain a succinic acid aqueous solution; based on the volume of the succinic acid stock solution being 1 L, the mass of the phosphate extractant is 2 to 55 g (for example, 2 g, 5 g, 8 g, 10 g, 12 g, 15 g, 18 g, 20 g, 22 g, 24 g, 26 g, 28 g, 30 g, 32 g, 34 g, 36 g, 38 g, 40 g, 42 g, 44 g, 46 g, 48 g, 50 g, 52 g, 54 g, 55 g or a range between any of the above values); based on the volume of the succinic acid-loaded organic phase being 1 L L, the mass of the water is 30-95g (for example, it can be 30g, 32g, 35g, 38g, 40g, 42g, 45g, 48g, 50g, 52g, 55g, 58g, 60g, 62g, 65g, 68g, 70g, 72g, 75g, 78g, 80g, 82g, 85g, 88g, 90g, 92g, 95g or the range between any of the above values); the phosphate ester extractant includes at least one of diethyl phosphate, diethyl phosphate or triethyl phosphate; the number of forward cross-flow extraction and reverse cross-flow extraction is each independently ≥1 time, for example, it can be 1 time, 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times or the range between any of the above values;

[0034] (4) passing the succinic acid aqueous solution obtained in step (3) through a cation exchange resin column at a flow rate of 0.5 to 2.5 BV / h (for example, 0.5 BV / h, 0.6 BV / h, 0.8 BV / h, 1 BV / h, 1.1 BV / h, 1.2 BV / h, 1.3 BV / h, 1.4 BV / h, 1.5 BV / h, 1.6 BV / h, 1.7 BV / h, 1.8 BV / h, 1.9 BV / h, 2 BV / h, 2.1 BV / h, 2.2 BV / h, 2.3 BV / h, 2.4 BV / h, 2.5 BV / h or any range between the above values), and eluting with water 2 to 7 times (for example, 3 times, 4 times, 5 times, 6 times or any range between the above values) the mass of the succinic acid aqueous solution to obtain a succinic acid effluent;

[0035] (5) decolorizing and filtering the succinic acid effluent obtained in step (4) with activated carbon to obtain a succinic acid filtrate; based on the volume of the succinic acid effluent as 1 L, the mass of the activated carbon is 0.5 to 10 g (for example, 0.5 g, 1 g, 2 g, 3 g, 4 g, 5 g, 5.2 g, 5.5 g, 5.8 g, 6 g, 6.2 g, 6.5 g, 6.8 g, 7 g, 7.2 g, 7.5 g, 7.8 g, 8 g, 8.5 g, 9 g, 9.5 g, 10 g or any range between the above values);

[0036] (5) The succinic acid filtrate obtained in step (4) is subjected to reduced pressure distillation and cooling crystallization to obtain the succinic acid composition.

[0037] Preferably, the activated carbon decolorization temperature is 60-85°C and the time is 30-80 minutes.

[0038] In the present invention, the filtration includes filtering using an ultrafiltration membrane; the pore size of the ultrafiltration membrane is 20 to 80 nm, for example, it can be 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm or 80 nm or a range between any of the above values.

[0039] Preferably, the filtration temperature is 40-60°C, for example, it can be 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C or a range between any of the above values.

[0040] In the present invention, the temperature of the reduced pressure distillation is 65 to 75°C, the pressure is -0.07 to -0.1MPa, and when the content of succinic acid is greater than 15wt%, the distillation is stopped; the concentrated succinic acid solution is placed at a low temperature (≤8°C) for cooling and crystallization to obtain the succinic acid composition.

[0041] In a second aspect, the present invention provides a polyester, wherein the raw materials for preparing the polyester include the succinic acid composition described in the first aspect.

[0042] Preferably, the polyester comprises an aliphatic polyester.

[0043] Preferably, the polyester comprises the following components:

[0044] Based on the total molar amount of component A being 100 mol%, the dicarboxylic acid compound comprising the following components:

[0045] a1, 65 to 100 mol % of succinic acid and / or its ester derivatives;

[0046] a2, 0 to 35 mol% of a derivative of a C6 to C14 dicarboxylic acid and / or its ester;

[0047] and component B: 1,4-butanediol in an amount at least equimolar to component A; the succinic acid is the succinic acid composition described in the first aspect.

[0048] In the present invention, the molar ratio of component B to component A is (1-3):1, for example, it can be 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1 or a range between any of the above values, more preferably (1-2):1.

[0049] In the present invention, the polyester comprising the following components means that the molecular structure of the polyester contains structural units derived from component A and structural units derived from component B; the dicarboxylic acid compound comprising the following components means that in the molecular structure of the polyester, the dicarboxylic acid structural unit part contains structural units derived from component a1 and structural units derived from component a2.

[0050] In the present invention, 65 to 100 mol%, for example, can be 65 mol%, 66 mol%, 68 mol%, 70 mol%, 72 mol%, 74 mol%, 76 mol%, 78 mol%, 80 mol%, 82 mol%, 84 mol%, 86 mol%, 88 mol%, 90 mol%, 92 mol%, 94 mol%, 96 mol%, 98 mol%, 100 mol% or the range between any of the above values.

[0051] In the present invention, 0-35 mol% can be, for example, 0 mol%, 2 mol%, 4 mol%, 6 mol%, 8 mol%, 10 mol%, 12 mol%, 14 mol%, 16 mol%, 18 mol%, 20 mol%, 22 mol%, 24 mol%, 26 mol%, 28 mol%, 30 mol%, 32 mol%, 34 mol%, 35 mol% or a range between any of the above values.

[0052] In the present invention, when component a1 is selected from derivatives of succinic acid esters, the succinic acid composition is used as a raw material to obtain the ester derivatives thereof.

[0053] Preferably, based on the total molar amount of component A being 100 mol%, the dicarboxylic acid compound comprising the following components:

[0054] a1, 72-82 mol% of succinic acid and / or its ester derivatives;

[0055] a2, 18 to 28 mol% of C6 to C14 dicarboxylic acid and / or its ester derivatives.

[0056] In the present invention, the derivatives of succinates include alkyl succinates. For example, the alkyl succinates may be at least one of dimethyl succinate, diethyl succinate, di-n-propyl succinate, diisopropyl succinate, di-n-butyl succinate, diisobutyl succinate, di-tert-butyl succinate, di-n-pentyl succinate, diisopentyl succinate, and di-n-hexyl succinate; the alkyl succinate may be an alkyl ester formed from succinic acid or an alkyl ester formed from succinic anhydride, preferably dimethyl succinate formed from succinic anhydride.

[0057] In the present invention, component a2 is selected from C6 to C14 straight-chain dicarboxylic acids, for example, it can be C6, C7, C8, C9, C10, C11, C12, C13, C14 straight-chain dicarboxylic acids, illustratively, including at least one of adipic acid, azelaic acid, sebacic acid or brazilic acid, preferably adipic acid and / or sebacic acid.

[0058] In the present invention, the derivatives of the C6-C14 dicarboxylic acid ester include C6-C14 dicarboxylic acid alkyl esters. For example, the alkyl ester may be at least one of dimethyl ester, diethyl ester, di-n-propyl ester, diisopropyl ester, di-n-butyl ester, diisobutyl ester, di-tert-butyl ester, di-n-pentyl ester, diisopentyl ester, and di-n-hexyl ester; the alkyl ester may be an alkyl ester formed by a diacid, or an alkyl ester formed by a diacid anhydride.

[0059] In the present invention, the derivatives of dicarboxylic acids or their esters may be used alone or in admixture of two or more.

[0060] Preferably, in the polyester, the mass content of sulfate is 90 to 210 ppm, for example, it can be 90 ppm, 95 ppm, 100 ppm, 105 ppm, 110 ppm, 115 ppm, 120 ppm, 125 ppm, 130 ppm, 135 ppm, 140 ppm, 145 ppm, 150 ppm, 155 ppm, 160 ppm, 165 ppm, 170 ppm, 175 ppm, 180 ppm, 185 ppm, 190 ppm, 195 ppm, 200 ppm, 205 ppm, 210 ppm or a range between any of the above values, more preferably 100 to 160 ppm.

[0061] Preferably, the mass content of phosphide in the polyester is 0.1 to 15 ppm, for example, it can be 0.1 ppm, 0.2 ppm, 0.5 ppm, 1 ppm, 2 ppm, 3 ppm, 4 ppm, 5 ppm, 6 ppm, 7 ppm, 8 ppm, 9 ppm, 10 ppm, 11 ppm, 12 ppm, 13 ppm, 14 ppm, 15 ppm or a range between any of the above values, more preferably 1 to 10 ppm.

[0062] In the present invention, a polyester having a low acid value and a high viscosity can be obtained by using the succinic acid composition as a raw material; in the present invention, according to the standard DIN EN 12634-1998, the acid value of the polyester is ≤1.2 mg KOH / g, for example, it can be 0.4 mg KOH / g, 0.5 mg KOH / g, 0.6 mg KOH / g, 0.7 mg KOH / g, 0.8 mg KOH / g, 0.9 mg KOH / g, 1 mg KOH / g, 1.1 mg KOH / g, 1.2 mg KOH / g or a range between any of the above values, and the acid value is further preferably ≤1 mg KOH / g, and the acid value is more preferably ≤0.85 mg KOH / g.

[0063] Preferably, according to standard GB / T 17931-1999, the intrinsic viscosity of the polyester is ≥1.4 dL / g, for example, it can be 1.4 dL / g, 1.45 dL / g, 1.5 dL / g, 1.55 dL / g, 1.6 dL / g, 1.65 dL / g, 1.7 dL / g, 1.75 dL / g, 1.8 dL / g, 1.9 dL / g or ranges between any of the above values, more preferably, the intrinsic viscosity is ≥1.52 dL / g, and more preferably, the intrinsic viscosity is ≥1.63 dL / g.

[0064] In the present invention, the polyester can be prepared by conventional technical methods in the art. Exemplarily, the method includes the following steps:

[0065] The components A and B are subjected to an esterification reaction at a temperature of 140 to 220° C. and a pressure of 0.5 to 2 bar for 1 to 6 hours to obtain an esterification product; the esterification product is subjected to a pre-condensation reaction at a temperature of 220 to 260° C. and a pressure of 0.1 to 1 bar for 40 to 120 minutes to obtain a pre-condensation product; and the pre-condensation product is subjected to a condensation reaction at a temperature of 230 to 280° C. and a pressure of 1 to 3 mbar for 120 to 180 minutes, sliced, and dried to obtain the polyester.

[0066] In the present invention, the raw materials for the esterification reaction also include a crosslinking agent, and the crosslinking agent includes at least one of tartaric acid, citric acid, malic acid, trimethylolpropane, trimethylolethane, pentaerythritol, polyether triol, glycerol, 1,3,5-trisic acid, 1,2,4-trisic acid, 1,2,4-trisic anhydride, 1,2,4,5-pyromellitic acid or pyromellitic dianhydride; based on the mass of the polyester finished product as 100wt%, the mass percentage of the crosslinking agent is 0.05-1wt%.

[0067] In the present invention, the esterification reaction and / or pre-polycondensation reaction further comprises a catalyst; the catalyst may be a tin compound, an antimony compound, a cobalt compound, a lead compound, a zinc compound, an aluminum compound or a titanium compound, more preferably a zinc compound, an aluminum compound or a titanium compound, and most preferably a titanium compound; the titanium compound may be tetrabutyl titanate or tetraisopropyl titanate; the total mass of the catalyst is 0.001 to 1 wt % of the mass of the polycondensation product.

[0068] In a third aspect, the present invention provides a polyester composite material, wherein the polyester composite material is a composite material obtained by extrusion processing; the polyester composite material comprises the polyester described in the second aspect.

[0069] Preferably, the polyester composite material further comprises at least one of polyhydroxyalkanoate, inorganic filler or auxiliary agent.

[0070] Preferably, the polyester composite material comprises, by weight, 40 to 65 parts of aliphatic polyester, 20 to 30 parts of polyhydroxyalkyl ester, 5 to 25 parts of inorganic filler and 0 to 1 part of auxiliary agent; the raw material for preparing the aliphatic polyester comprises the succinic acid composition according to the first aspect, or the aliphatic polyester comprises the polyester according to the second aspect.

[0071] In the present invention, 40 to 65 parts of the aliphatic polyester can be, for example, 40 parts, 42 parts, 44 parts, 46 parts, 48 ​​parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 65 parts or a range between any of the above values.

[0072] In the present invention, 20 to 30 parts of the polyhydroxyalkyl ester may be, for example, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts or any range between the above values.

[0073] In the present invention, 5 to 25 parts of the inorganic filler can be, for example, 5 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 25 parts or any range between the above values.

[0074] In the present invention, 0 to 1 part of the auxiliary agent can be, for example, 0 part, 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part, 1 part or a range between any of the above values.

[0075] Preferably, the polyhydroxyalkanoate comprises polylactic acid and / or poly-β-hydroxybutyrate.

[0076] Preferably, the inorganic filler includes at least one of talc, calcium carbonate, barium sulfate, montmorillonite or kaolin.

[0077] In the present invention, the auxiliary agent includes but is not limited to an antioxidant; the antioxidant includes but is not limited to antioxidant 1010.

[0078] In the present invention, the polyester composite material is continuously produced in a twin-screw extruder for 168 hours, and the screw wear percentage (η) is ≤0.5%, preferably η≤0.4%, more preferably η≤0.29%, and particularly preferably η≤0.13%.

[0079] The polyester and polyester composite material of the present invention are also biodegradable.

[0080] For the purposes of the present invention, a substance or a mixture of substances is characterized as "biodegradable" if it shows a percentage degree of biodegradation, as defined in DIN EN 13432, of at least 90%.

[0081] Biodegradation generally results in the decomposition of the polyester or polyester blend within a reasonable period of time. Degradation can occur via enzymatic, hydrolytic or oxidative pathways and / or, by exposure to electromagnetic radiation such as ultraviolet radiation, most often by exposure to microorganisms such as bacteria, yeasts, fungi or algae. Biodegradability can be quantified by mixing the polyester with compost and storing it for a specific period of time. For example, according to DIN EN 13432, during the composting process, CO2-free air is introduced into the mature compost and the compost is subjected to a specific temperature course. Here, biodegradability is defined as the percentage degree of biodegradation expressed as the ratio of the net amount of CO2 released by the sample (after deducting the amount of CO2 released by the compost without the sample) to the maximum amount of CO2 that the sample can release (calculated from the carbon content of the sample).

[0082] Additionally, other methods for determining biodegradability are described in ASTM D5338 and ASTM D6400.

[0083] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0084] Compared with the prior art, the present invention has the following beneficial effects:

[0085] The succinic acid composition provided by the present invention is compounded with a compound containing a sulfate group in a specific content and a phosphorus compound, and the succinic acid composition is used as a raw material to prepare polyester, thereby ensuring the production efficiency of the polyester and obtaining a polyester with a low acid value and high viscosity; and reducing the degree of corrosion of the polyester on metal equipment, thereby ensuring the quality of the polyester material. DETAILED DESCRIPTION

[0086] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0087] If not otherwise specified, the raw materials used in the present invention are as follows:

[0088] 1,4-Butanediol: purchased from Xinjiang Meike Chemical Co., Ltd.;

[0089] Commercially available succinic acid, superior product specifications: purchased from Shandong Feiyang Chemical Co., Ltd., succinic acid mass content 99.78%, SO4 2- Content 47ppm, phosphorus content 0ppm; Glycerin: purchased from Aladdin;

[0090] Tetrabutyl titanate: purchased from Jianyi Chemical Import & Export Co., Ltd.;

[0091] Polylactic acid: PLA 3001D, purchased from Natureworks;

[0092] Talc: HTPultra5 L, purchased from IMIFABI;

[0093] Calcium carbonate: OM-2T, purchased from Omya Corporation.

[0094] In the present invention, SO4 2- The content was determined according to SN / T 2994-2011 standard using ion chromatography.

[0095] The phosphorus content test refers to US EPA method 3052:1996, using ICP-OES analysis and measuring according to the following procedure: weigh about 0.1g of the succinic acid composition, add 5mL of nitric acid to completely immerse the succinic acid composition, then drop 1.0mL of hydrogen peroxide to react for 2min, seal in a microwave digestion tank and digest at 210°C for 3 hours, after cooling to room temperature, filter with a 0.45μm filter membrane, dilute with distilled water to 50mL, and test by ICP-OES.

[0096] In the present invention, the test method for the mass content of succinic acid in the succinic acid composition is tested with reference to the method for determining the succinic acid content in section 4.3 of GB / T34686-2017.

[0097] Examples 1 to 6, Comparative Examples 1 to 4

[0098] Examples 1 to 6 and Comparative Examples 1 to 4 respectively provide a succinic acid composition comprising succinic acid, sulfate and a phosphorus compound; in the succinic acid composition, the mass contents of succinic acid, sulfate and phosphorus compound are shown in Table 1.

[0099] The mass content of sulfate is represented by the mass content of sulfate ions, and the mass content of phosphorus compounds is represented by the mass content of phosphorus elements.

[0100] The succinic acid compositions provided in Examples 1 to 3, Example 5, Example 6, and Comparative Example 2 are compositions formed by succinic acid and sulfates and phosphorus compounds remaining in succinic acid during the preparation of succinic acid; the succinic acid compositions provided in Example 4, Comparative Example 1, Comparative Example 3, and Comparative Example 4 are compositions formed by adding sodium sulfate and / or sodium dihydrogen phosphate to commercially available succinic acid (superior specifications of Shandong Feiyang Chemical Co., Ltd.), and succinic acid, and the remainder of the composition is water and other impurity acids remaining in the preparation of the succinic acid composition.

[0101] Comparative Example 5

[0102] This comparative example provides a succinic acid purchased from Shandong Feiyang Chemical Co., Ltd. with superior specifications.

[0103] Table 1

[0104]

[0105] The preparation methods of the succinic acid compositions provided in Examples 1 to 3, Example 5, Example 6, and Comparative Example 2 are as follows.

[0106] Example 1

[0107] This embodiment provides a succinic acid composition, and the preparation method thereof comprises:

[0108] (1) using biomass resources as raw materials, preparing succinic acid fermentation broth by fermentation, the fermentation broth is prepared by conventional methods in the art, for example, it can be prepared by referring to the method in CN118459331A, after the fermentation broth is filtered to remove cells, adding excess calcium hydroxide to the fermentation clear liquid until no more calcium succinate precipitate is produced in the succinic acid fermentation broth, filtering and separating to obtain calcium succinate precipitate;

[0109] (2) adding concentrated sulfuric acid to the calcium succinate obtained in step (1) for acidification, adjusting the pH value of the system to 2.3, and obtaining a succinic acid stock solution having a succinic acid content of 72 g / L;

[0110] (3) adding 26 g of diisooctyl phosphate to the succinic acid stock solution obtained in step (2) based on a volume of 1 L to perform extraction three times to obtain a succinic acid-loaded organic phase; then, based on a volume of 1 L of the succinic acid-loaded organic phase, using 55 g of deionized water to perform three-stage reverse extraction on the succinic acid-loaded organic phase to obtain a succinic acid aqueous solution;

[0111] (4) passing the succinic acid aqueous solution obtained in step (3) through a 732 type cation exchange resin column at a flow rate of 1.6 BV / h, and eluting with water 3 times the mass of the succinic acid aqueous solution to obtain a succinic acid effluent;

[0112] (5) decolorizing the succinic acid effluent obtained in step (4) with activated carbon at 75° C. for 60 min, wherein the mass of the activated carbon is 8 g (i.e., the mass of the activated carbon is 8 g / L) based on the volume of the succinic acid effluent being 1 L; and then filtering at 50° C. using an ultrafiltration membrane with a pore size of 40 nm to obtain a succinic acid filtrate;

[0113] (6) The succinic acid filtrate obtained in step (5) is subjected to reduced pressure distillation, the distillation temperature is controlled at 70° C., and the pressure is -0.07 to -0.1 MPa. When the succinic acid content is greater than 15 wt %, the distillation is stopped, and the concentrated succinic acid solution is placed at a low temperature (4° C.) for cooling and crystallization to obtain white succinic acid crystals, that is, the succinic acid composition.

[0114] Example 2

[0115] The present embodiment provides a succinic acid composition, wherein steps (1) and (2) of the preparation method are the same as those of embodiment 1, except that: (3) adding 26 g of diisooctyl phosphate to the succinic acid stock solution obtained in step (2) based on a volume of 1 L to perform extraction four times to obtain a succinic acid-loaded organic phase; then, based on a volume of 1 L of the succinic acid-loaded organic phase, using 70 g of deionized water to perform four-stage reverse extraction on the succinic acid-loaded organic phase to obtain a succinic acid aqueous solution;

[0116] (4) passing the succinic acid aqueous solution obtained in step (3) through a 732 type cation exchange resin column at a flow rate of 1.5 BV / h, and eluting with water 4 times the mass of the succinic acid aqueous solution to obtain a succinic acid effluent;

[0117] (5) decolorizing the succinic acid effluent obtained in step (4) with activated carbon at 75° C. for 60 min, wherein the mass of the activated carbon is 8 g (i.e., the mass of the activated carbon is 8 g / L) based on the volume of the succinic acid effluent being 1 L; and then filtering at 50° C. using an ultrafiltration membrane with a pore size of 40 nm to obtain a succinic acid filtrate;

[0118] (6) The succinic acid filtrate obtained in step (5) is subjected to reduced pressure distillation, the distillation temperature is controlled at 70° C., and the pressure is -0.07 to -0.1 MPa. When the succinic acid content is greater than 15 wt %, the distillation is stopped, and the concentrated succinic acid solution is placed at a low temperature (4° C.) for cooling and crystallization to obtain white succinic acid crystals, that is, the succinic acid composition.

[0119] Example 3

[0120] This embodiment provides a succinic acid composition, wherein steps (1) and (2) in the preparation method are the same as those in Example 1, except for the following steps:

[0121] (3) adding 17 g of diethyl phosphate to the succinic acid stock solution obtained in step (2) based on a volume of 1 L to perform extraction three times to obtain a succinic acid-loaded organic phase; then, based on a volume of 1 L of the succinic acid-loaded organic phase, using 65 g of deionized water to perform three-stage reverse extraction on the succinic acid-loaded organic phase to obtain a succinic acid aqueous solution;

[0122] (4) passing the succinic acid aqueous solution obtained in step (3) through a 732 type cation exchange resin column at a flow rate of 1.4 BV / h, and eluting with water 5 times the mass of the succinic acid aqueous solution to obtain a succinic acid effluent;

[0123] (5) decolorizing the succinic acid effluent obtained in step (4) with activated carbon at 70° C. for 60 min, wherein the mass of the activated carbon is 7 g (i.e., the mass of the activated carbon is 7 g / L) based on the volume of the succinic acid effluent being 1 L; and then filtering at 50° C. using an ultrafiltration membrane with a pore size of 40 nm to obtain a succinic acid filtrate;

[0124] (6) The succinic acid filtrate obtained in step (5) is subjected to reduced pressure distillation, the distillation temperature is controlled at 70° C., and the pressure is -0.07 to -0.1 MPa. When the succinic acid content is greater than 15 wt %, the distillation is stopped, and the concentrated succinic acid solution is placed at a low temperature (4° C.) for cooling and crystallization to obtain white succinic acid crystals, that is, the succinic acid composition.

[0125] Example 5

[0126] This embodiment provides a succinic acid composition, wherein step (1) of the preparation method thereof is the same as that of embodiment 1, except that:

[0127] (2) adding concentrated sulfuric acid to the calcium succinate obtained in step (1) for acidification, adjusting the pH value of the system to 1.6, and obtaining a succinic acid stock solution having a succinic acid content of 68 g / L;

[0128] (3) adding 5 g of triethyl phosphate to the succinic acid stock solution obtained in step (2) based on a volume of 1 L to perform two extractions to obtain a succinic acid-loaded organic phase; then, based on a volume of 1 L of the succinic acid-loaded organic phase, using 50 g of deionized water to perform two-stage reverse extractions on the succinic acid-loaded organic phase to obtain a succinic acid aqueous solution;

[0129] (4) passing the succinic acid aqueous solution obtained in step (3) through a 732 type cation exchange resin column at a flow rate of 1.7 BV / h, and eluting with water 4 times the mass of the succinic acid aqueous solution to obtain a succinic acid effluent;

[0130] (5) decolorizing the succinic acid effluent obtained in step (4) with activated carbon at 70° C. for 60 min, wherein the mass of the activated carbon is 8 g (i.e., the mass of the activated carbon is 8 g / L) based on the volume of the succinic acid effluent being 1 L; and then filtering at 50° C. using an ultrafiltration membrane with a pore size of 40 nm to obtain a succinic acid filtrate;

[0131] (6) The succinic acid filtrate obtained in step (5) is subjected to reduced pressure distillation, the distillation temperature is controlled at 70° C., and the pressure is -0.07 to -0.1 MPa. When the succinic acid content is greater than 15 wt %, the distillation is stopped, and the concentrated succinic acid solution is placed at a low temperature (4° C.) for cooling and crystallization to obtain white succinic acid crystals, that is, the bio-based succinic acid composition.

[0132] Example 6

[0133] This embodiment provides a succinic acid composition, wherein step (1) of the preparation method thereof is the same as that of embodiment 1, except that:

[0134] (2) adding concentrated sulfuric acid to the calcium succinate obtained in step (1) for acidification, adjusting the pH value of the system to 2.7, and obtaining a succinic acid stock solution having a succinic acid content of 77 g / L;

[0135] (3) adding 21 g of diethyl phosphate to the succinic acid stock solution obtained in step (2) based on a volume of 1 L to perform extraction three times to obtain a succinic acid-loaded organic phase; then, based on a volume of 1 L of the succinic acid-loaded organic phase, using 60 g of deionized water to perform a second-stage reverse extraction on the succinic acid-loaded organic phase to obtain a succinic acid aqueous solution;

[0136] (4) passing the succinic acid aqueous solution obtained in step (3) through a 732 type cation exchange resin column at a flow rate of 1.4 BV / h, and eluting with water 6 times the mass of the succinic acid aqueous solution to obtain a succinic acid effluent;

[0137] (5) decolorizing the succinic acid effluent obtained in step (4) with activated carbon at 75° C. for 70 min, wherein the mass of the activated carbon is 8 g (i.e., the mass of the activated carbon is 8 g / L) based on the volume of the succinic acid effluent being 1 L; and then filtering at 50° C. using an ultrafiltration membrane with a pore size of 40 nm to obtain a succinic acid filtrate;

[0138] (6) The succinic acid filtrate obtained in step (5) is subjected to reduced pressure distillation, the distillation temperature is controlled at 70° C., and the pressure is -0.07 to -0.1 MPa. When the succinic acid content is greater than 15 wt %, the distillation is stopped, and the concentrated succinic acid solution is placed at a low temperature (4° C.) for cooling and crystallization to obtain white succinic acid crystals, that is, the bio-based succinic acid composition.

[0139] Comparative Example 2

[0140] This comparative example provides a succinic acid composition, wherein step (1) of the preparation method thereof is the same as that of Example 1, except that:

[0141] (2) adding concentrated sulfuric acid to the calcium succinate obtained in step (1) for acidification, adjusting the pH value of the system to 1.1, and obtaining a succinic acid stock solution having a succinic acid content of 68 g / L;

[0142] (3) adding 30 g of diethyl phosphate to the succinic acid stock solution obtained in step (2) based on a volume of 1 L, and performing extraction three times to obtain a succinic acid-loaded organic phase; then, based on a volume of 1 L of the succinic acid-loaded organic phase, using 60 g of deionized water to perform a second-stage reverse extraction on the succinic acid-loaded organic phase to obtain a succinic acid aqueous solution;

[0143] (4) passing the succinic acid aqueous solution obtained in step (3) through a 732 type cation exchange resin column at a flow rate of 1.6 BV / h, and eluting with water 3 times the mass of the succinic acid aqueous solution to obtain a succinic acid effluent;

[0144] (5) decolorizing the succinic acid effluent obtained in step (4) with activated carbon at 70° C. for 55 min, wherein the mass of the activated carbon is 8 g (i.e., the mass of the activated carbon is 8 g / L) based on the volume of the succinic acid effluent being 1 L; and then filtering at 50° C. using an ultrafiltration membrane with a pore size of 40 nm to obtain a succinic acid filtrate;

[0145] (6) The succinic acid filtrate obtained in step (5) is subjected to reduced pressure distillation, the distillation temperature is controlled at 70° C., and the pressure is -0.07 to -0.1 MPa. When the succinic acid content is greater than 15 wt %, the distillation is stopped, and the concentrated succinic acid solution is placed at a low temperature (4° C.) for cooling and crystallization to obtain white succinic acid crystals, that is, the succinic acid composition.

[0146] Application Example 1

[0147] This application example provides a polyester, wherein the raw materials for preparing the polyester include 350 kg of butanediol, 340 kg of succinic acid, 1.2 kg of glycerol and 0.47 kg of tetrabutyl titanate; the succinic acid is the succinic acid composition provided in Example 1; and the preparation method of the polyester includes the following steps:

[0148] (1) physically mixing succinic acid, 1,4-butanediol and glycerol, and after the mixing is completed, transferring the obtained mixture to an esterification reactor, and subjecting the reaction mixture to an esterification reaction at a temperature of 180° C. and a pressure of 1.0 bar for 3 hours to obtain an esterification product;

[0149] (2) transferring the esterification product obtained in step (1) to a vertical reactor with stirring, adding tetrabutyl titanate, and carrying out a pre-condensation reaction at a temperature of 245° C. and a pressure of 0.36 bar for 85 minutes to obtain a pre-condensation product;

[0150] (3) The prepolymer product obtained in step (2) is transferred to a horizontal reactor with stirring, and polycondensed for 150 min at a temperature of 248° C. and a pressure of 2.0 mbar, sliced, and dried to obtain the polyester.

[0151] Application Examples 2 to 6

[0152] Application Examples 2 to 6 respectively provide a polyester, which differs from Application Example 1 only in that the succinic acid is the succinic acid composition provided in Examples 2 to 6, and other raw materials, dosages and preparation methods are the same as those in Application Example 1.

[0153] Application Example 7

[0154] Application Example 7 provides a polyester, which is different from Application Example 1 in that the total molar amount of the dibasic acid remains unchanged, including 75 mol% of succinic acid and 25 mol% of sebacic acid, and the succinic acid is the succinic acid composition provided in Example 1; the raw materials for preparing the polyester also include 350 kg of butanediol, 2.2 kg of glycerol and 0.5 kg of tetrabutyl titanate; the preparation method of the polyester includes the following steps:

[0155] (1) physically mixing succinic acid, sebacic acid, 1,4-butanediol and glycerol, and after the mixing is completed, transferring the obtained mixture to an esterification reactor, and subjecting the reaction mixture to an esterification reaction at a temperature of 210° C. and a pressure of 1.2 bar for 5 hours to obtain an esterified product;

[0156] (2) transferring the esterification product obtained in step (1) to a vertical reactor with stirring, adding tetrabutyl titanate, and performing a pre-condensation reaction at a temperature of 255° C. and a pressure of 0.56 bar for 100 minutes to obtain a pre-condensation product;

[0157] (3) The prepolymer product obtained in step (2) is transferred to a horizontal reactor with stirring, and polycondensed for 125 min at a temperature of 250° C. and a pressure of 1.0 mbar, sliced, and dried to obtain the polyester.

[0158] Application Example 8

[0159] Application Example 8 provides a polyester, which is different from Application Example 1 in that the total molar amount of the dibasic acid remains unchanged, including 68 mol% of succinic acid and 32 mol% of sebacic acid, and the succinic acid is the succinic acid composition provided in Example 1; the raw materials for preparing the polyester also include 350 kg of butanediol, 2.5 kg of glycerol and 0.55 kg of tetrabutyl titanate; the preparation method of the polyester includes the following steps:

[0160] (1) physically mixing succinic acid, sebacic acid, 1,4-butanediol and glycerol, and after the mixing is completed, transferring the obtained mixture to an esterification reactor, and subjecting the reaction mixture to an esterification reaction at a temperature of 200° C. and a pressure of 1.8 bar for 2 hours to obtain an esterified product;

[0161] (2) transferring the esterification product obtained in step (1) to a vertical reactor with stirring, adding tetrabutyl titanate, and carrying out a pre-polycondensation reaction at a temperature of 255° C. and a pressure of 0.3 bar for 110 minutes to obtain a pre-polycondensation product;

[0162] (3) The prepolymer product obtained in step (2) is transferred to a horizontal reactor with stirring, and polycondensed for 130 min at a temperature of 255° C. and a pressure of 1.5 mbar, sliced, and dried to obtain the polyester.

[0163] Application Example 9

[0164] Application Example 9 provides a polyester, which differs from Application Example 1 only in that the total molar amount of the dibasic acid remains unchanged, including 75 mol% of succinic acid and 25 mol% of adipic acid, and other raw materials, amounts and preparation methods are the same as those in Application Example 1.

[0165] Comparative Application Examples 1 to 5

[0166] Comparative Application Examples 1 to 5 respectively provide a polyester, which differs from Application Example 1 only in that the succinic acid is the succinic acid composition provided in Comparative Examples 1 to 4 and the succinic acid provided in Comparative Example 5, and other raw materials, amounts and preparation methods are the same as those in Application Example 1.

[0167] Test the acid value, viscosity, SO4 of the polyester provided in Application Examples 1 to 9 and Comparative Application Examples 1 to 5 2- content and phosphorus content.

[0168] The acid value test method includes: determining the acid value AN (mg KOH / g) of the sample according to the DIN EN 12634 standard of October 1998.

[0169] The solvent mixture used includes: 1 part by volume of dimethyl sulfoxide, 8 parts by volume of isopropanol and 7 parts by volume of toluene, and the volume of the solvent mixture is 150 mL.

[0170] According to the provisions of DIN EN 12634, the sample is pre-titrated to determine the appropriate sample mass and ensure that the volume of the consumed titrant is 2-3mL. The sample is added to the solvent mixture and heated to 70-85°C to dissolve all the samples into a clear solution. During the titration, the solution temperature is maintained at 65-75°C to avoid sample precipitation. If appropriate, tetrabutylammonium hydroxide is used as the titrant, and the highly toxic tetramethylammonium hydroxide is avoided. At the same time, in order to prevent the solvent mixture from absorbing CO2 in the air and thus affecting the volume of the blank solvent consumed titrant, when testing the volume of the blank solvent consumed titrant, the blank solvent should be pre-treated according to the same process as the sample test operation, such as heating the blank solvent for the same time and temperature, and then titrating the blank solvent.

[0171] The viscosity test method includes: according to GB / T 17931-1999, the viscosity is measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C, and the sample concentration is 5 mg / mL.

[0172] SO4 2- The test methods for the content of magnesium and phosphorus are as described above.

[0173] The specific test results are shown in Table 2, where ND means not detected.

[0174] Table 2

[0175]

[0176] It can be seen from Table 2 that the polyester prepared using the succinic acid composition provided by the present invention as a raw material has a low acid value and a high viscosity; the acid value of the polyester is ≤1.18 mg KOH / g, and the viscosity is ≥1.45 dL / g.

[0177] It can be seen from the comparative application examples that the sulfate content and phosphorus content in the succinic acid composition are not within a specific range, and a polyester with a low acid value and a high viscosity cannot be obtained at the same time.

[0178] Application examples 2-1 to 2-12, comparative application examples 2-1 to 2-5

[0179] Application Examples 2-1 to 2-12 and Comparative Application Examples 2-1 to 2-5 respectively provide a polyester composite material. The formulas of the polyester composite materials are shown in Tables 3 and 4 in parts by weight, wherein “ / ” indicates that the component is not included in the formula.

[0180] Table 3

[0181]

[0182] Table 4

[0183]

[0184] Performance Testing

[0185] Before processing, the screw surface of the extruder is cleaned with cotton cloth, and the diameter of the middle position of the screw is tested with a caliper. The test is carried out three times in parallel, and the average value is taken, which is recorded as D0 (unit mm); the polyester composite materials provided by application examples 2-1 to 2-12 and comparative application examples 2-1 to 2-5 are respectively processed in a twin-screw extruder. After continuous production in the twin-screw extruder for 168 hours, the screw surface is cleaned with cotton cloth, and the diameter of the screw at the same position before processing is tested with a caliper. The test is carried out three times in parallel, and the average value is taken, which is recorded as D1 (unit mm); the corrosion degree of the screw of the twin-screw extruder is characterized by the change in the screw diameter before and after processing, and the screw wear percentage η is calculated, η=(ΔD / D0)×100%; wherein ΔD=D0-D1, unit mm. The larger the screw wear percentage η, the more serious the screw corrosion is.

[0186] Among them, the process parameters of the twin-screw extruder are:

[0187] The temperatures in different intervals are: 170℃-180℃-180℃-180℃-190℃-190℃-200℃-200℃-200℃-180℃; the feeding speed is 800kg / h; the vacuum pressure is -0.07~-0.1MPa.

[0188] The specific test results are shown in Table 5.

[0189] Table 5

[0190] η / % Application Example 2-1 0.19 Application Example 2-2 0.08 Application Example 2-3 0.39 Application Example 2-4 0.13 Application Example 2-5 0.40 Application Example 2-6 0.48 Application Example 2-7 0.18 Application Example 2-8 0.16 Application Example 2-9 0.16 Application Example 2-10 0.29 Application Example 2-11 0.16 Application Example 2-12 0.18 Comparative Application Example 2-1 0.73 Comparative Application Example 2-2 0.55 Comparative Application Example 2-3 0.56 Comparative Application Example 2-4 0.82 Comparative Application Example 2-5 1.18

[0191] As can be seen from Table 5, the polyester composite material formed by the polyester prepared using the succinic acid composition provided by the present invention as a raw material is continuously produced in a twin-screw extruder for 168 hours, and the screw wear percentage of the twin-screw extruder is less than or equal to 0.5%, which can significantly reduce the corrosion of the polyester material to metal equipment.

[0192] However, for the polyester composition provided in the comparative application example, after 168 hours of continuous production, the screw diameter changed significantly, and the polyester composite material caused serious corrosion to the equipment.

[0193] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A succinic acid composition, characterized in that The succinic acid composition comprises succinic acid, a compound containing a sulfate group and a phosphorus compound; The mass content of sulfate in the succinic acid composition is 240 to 500 ppm; The mass content of phosphorus in the succinic acid composition is 0.5-40 ppm.

2. The succinic acid composition according to claim 1, characterized in that The mass content of sulfate in the succinic acid composition is 320 to 480 ppm, preferably 370 to 420 ppm.

3. The succinic acid composition according to claim 1 or 2, characterized in that The mass content of phosphorus in the succinic acid composition is 2 to 25 ppm, more preferably 5 to 20 ppm.

4. The succinic acid composition according to any one of claims 1 to 3, characterized in that The sulfate-containing compound includes sulfuric acid and / or sulfate; Preferably, the sulfate includes any one or at least two of sodium sulfate, magnesium sulfate, potassium sulfate or iron sulfate; Preferably, the phosphorus compound comprises any one or at least two of nucleic acid, phospholipid, dioctyl phosphate, diethyl phosphate, triethyl phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphoric acid, phosphorous acid or sodium phosphate; Preferably, the mass percentage of succinic acid in the succinic acid composition is ≥99.5%, more preferably ≥99.7%.

5. A polyester, characterized in that The raw material for preparing the polyester comprises the succinic acid composition according to any one of claims 1 to 4.

6. The polyester according to claim 5, characterized in that The polyester comprises the following components: Component A: Based on the total molar amount of component A being 100 mol%, the dicarboxylic acid compound comprising the following components: a1, 65 to 100 mol % of a derivative of succinic acid and / or its ester, a2, 0 to 35 mol% of a derivative of a C6 to C14 dicarboxylic acid and / or its ester; and Component B: 1,4-butanediol in an amount at least equal in molar amount to component A; The succinic acid is the succinic acid composition according to any one of claims 1 to 4.

7. The polyester according to claim 5 or 6, characterized in that In the polyester, the mass content of sulfate is 90 to 210 ppm; Preferably, the mass content of phosphorus in the polyester is 0.1 to 15 ppm.

8. A polyester composite material, characterized in that: The polyester composite material is a composite material obtained by extrusion processing; The polyester composite material comprises the polyester according to any one of claims 5 to 7.

9. The polyester composite material according to claim 8, characterized in that: The polyester composite material further comprises at least one of polyhydroxyalkanoic acid ester, inorganic filler or auxiliary agent.

10. The polyester composite material according to claim 8 or 9, characterized in that: The polyester composite material is continuously produced in a twin-screw extruder for 168 hours, and the screw wear percentage is ≤0.5%.

Citation Information

Patent Citations

  • Biomass-resource-derived polyester and production process thereof

    CN103183813A

  • Production of oxygen-containing compound

    JP1999113588A

  • Process for the production of succinic acid by anaerobic fermentation

    US5143833A

  • Process for making succinic acid, microorganisms for use in the process and methods of obtaining the microorganisms

    US5504004A

  • Mutant E. coli strain with increased succinic acid production

    US5770435A

Cited By

  • Polyester and preparation method thereof

    CN121181860A

  • Aliphatic polyester, polyester composition containing same, and use thereof

    EP4806936A1

  • Aliphatic polyester, polyester composition containing same, and use thereof

    EP4806937A1